Interrogativity: Problematological Model and Applied Technique - Cosmin-Constantin BĂIAȘ (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Our paper deals with interrogativity from a philosophical as well as an educational perspective. Firstly, the rhetorical-argumentative theory of problematology is presented from the philosophical perspective of the problematological model. On the other hand, the question formulation technique shows a possible connection with educational or academic practice. What is finally obtained from connecting the two, through problematology as a philosophical construction and education as a practice of questioning, is that different ways of reasoning are encouraged and used in the socio-humanistic disciplines: creative thinking, critical thinking and thinking through questions.